Two new species of Fistulina (Agaricales, Basidiomycota) from the Northern Hemisphere - Zhou, Meng; Liu, Zhan-Bo; Lim, Young Woon; Cho, Yoonhee; Yang, Rui-Heng; Bao, Da-Peng; Zhao, Chang-Lin; Li, De-Wei; Vlasák, Josef; Dai, Yu-Cheng (Frontiers in Microbiology, 2022)
Phylogenetic and morphological analyses on samples of Fistulina from East Asia and North America were carried out, and two new species were described, namely, Fistulina americana and Fistulina orientalis, both previously known as Fistulina hepatica. The former is characterized by lateral stipitate basidiocarps, relatively small pores (7–8 per mm), a monomitic hyphal system with both clamp connections and simple septa, and ellipsoid basidiospores of 4–4.8 × 3–3.3 μm, and the species has been found on Quercus in North-East USA. F. orientalis is characterized by lateral stipitate basidiocarps, very small pores (11–12 per mm) with pruinose dissepiments, a monomitic hyphal system with both clamp connections and simple septa, and ovoid to subglobose basidiospores of 3–4 × 2.7–3 μm, and the species has been found on Castanopsis in East Asia. Phylogenetically, samples of F. americana and F. orientalis form two new lineages nested in the Fistulina clade.